The Cambridge handbook of smart contracts, blockchain technology and digital platforms / edited by Larry A. DiMatteo, Michel Cannarsa, Cristina Poncibò. - DiMatteo, Larry A.; Cannarsa, Michel; Poncibò, Cristina (Cambridge University Press, 2020)
The product of a unique collaboration between academic scholars, legal practitioners, and technology experts, this Handbook is the first of its kind to analyze the ongoing evolution of smart contracts, based upon blockchain technology, from the perspective of existing legal frameworks - namely, contract law. The book's coverage ranges across many areas of smart contracts and electronic or digital platforms to illuminate the impact of new, and often disruptive, technologies on the law. With a mix of scholarly commentary and practical application, chapter authors provide expert insights on the core issues involving the use of smart contracts, concluding that smart contracts cannot supplant contract law and the courts, but leaving open the question of whether there is a need for specialized regulations to prevent abuse. This book should be read by anyone interested in the disruptive effect of new technologies on the law generally, and contract law in particular.